Moisture Sources for Wintertime Extreme Precipitation Events Over South China During 1979–2013. Issue 13 (2nd July 2018) - Huang, Wenyu; He, Xinsheng; Yang, Zifan; Qiu, Tianpei; Wright, Jonathon S.; Wang, Bin; Lin, Daiyu
Abstract: A Lagrangian approach is applied to explore the evaporative moisture sources within the boundary layer for 103 wintertime extreme precipitation events over South China during 1979–2013. Oceanic sources provided about 67.7% of the moisture for these extreme precipitation events, with terrestrial sources providing the remaining parts. The five most important moisture source regions were the South China Sea (30.9% of the total moisture source within boundary layer), the western North Pacific (20.2%), the East China Sea (14.9%), South China (i.e., moisture recycling, in which local evapotranspiration supplies moisture for precipitation; 14.6%), and southeastern Asia (11.5%). Characteristic trajectories linking moisture from the key source regions to South China are identified. All of these trajectories entered China south of the Yangtze River, with characteristic time scales ranging from 2.8 to 5.7 days. The critical circulation patterns for moisture transport from different source regions are also determined. Cyclonic anomalies over South China and its surrounding continental areas favored moisture transport from the South China Sea and southeastern Asia. To leading order, changes in the relative contributions of these and other key moisture source regions were associated with changes in the location or development pattern of these cyclonic anomalies. Beyond these relationships, the presence of anticyclonic anomalies over the western North Pacific favored moisture transport from the western North Pacific, while the absence of these anomalies favored moisture recycling within South China and moisture transport from the East China Sea. Key Points: Moisture supply from the South China Sea played a leading role in wintertime extreme precipitation events over South China Moisture delivered from the South China Sea reflected a mixture of moisture originating over the South China Sea and western North Pacific Characteristic transport time scales for moisture from the key source regions ranged from 2.8 to 5.7 days